Necrosis progresiva bacteriana sinérgica - Morelli Brum, Raúl; Torterolo, Edgardo; Pomi, Jorge; de Vecchi, Jorge; Fernández Perdomo, Gonzalo; Fischer, Tabaré Mario (Cirugía del Uruguay, 1977)
Progressi ve bacterian syner gic necrosis has been known far over 70 years and seve ra! authors. Have written papers on this disease. A review of available bib!iography and the study of 6 personal observations over a two-year period, has -esulted in this attempt to update information on this disease and to describe it in ou- country, where no observations were found. It is a rare malady, which generally affects patients prior infirmities, generally caused by bacterian synergism between an aerobian and an anaerobian germ which resuHs in practically simultaneous skin and subcutaneous tissue necrosis, which developslowly, while the patient's condition remaing that of the initial stages. Morbility and death-rate are high if it is not detected in time. Elective treatment is su